2020
DOI: 10.1017/s136898002000230x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mediterranean diet and the Dietary Approach Stop Hypertension in reducing the risk of 10-year fatal and non-fatal CVD events in healthy adults: the ATTICA Study (2002–2012)

Abstract: Objective: To compare the Mediterranean and Dietary Approaches to Stop Hypertension (DASH) diets in deterring 10-year CVD. Design: Prospective cohort (n 2020) with a 10-year follow-up period for the occurrence of combined (fatal or non-fatal) CVD incidence (International Classification of Diseases (ICD)-10). Baseline adherence to the Mediterranean and DASH diets was assessed via a semi-quantitative FFQ according to the MedDietScore and DASH scores, respectively. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Recently, MD has been suggested to be beneficial in preventing and improving CVD [ 26 ]. In the study of Critselis E, et al, they found that high adherence to the MD was associated with a lower 10-year risk of fatal and non-fatal CVD [ 27 ]. Consistent with established studies [ 25 , 27 ], our study also indicated the risk of CVD for individuals with independent RA was 2.65 times than non-RA individuals, and the risk of CVD decreased as adherence to the MD increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, MD has been suggested to be beneficial in preventing and improving CVD [ 26 ]. In the study of Critselis E, et al, they found that high adherence to the MD was associated with a lower 10-year risk of fatal and non-fatal CVD [ 27 ]. Consistent with established studies [ 25 , 27 ], our study also indicated the risk of CVD for individuals with independent RA was 2.65 times than non-RA individuals, and the risk of CVD decreased as adherence to the MD increased.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Critselis E, et al, they found that high adherence to the MD was associated with a lower 10-year risk of fatal and non-fatal CVD [ 27 ]. Consistent with established studies [ 25 , 27 ], our study also indicated the risk of CVD for individuals with independent RA was 2.65 times than non-RA individuals, and the risk of CVD decreased as adherence to the MD increased. As pointed out by Johansson et al, [ 28 ] there was an inverse association between MD and RA risk among only men or in seropositive RA.…”
Section: Discussionmentioning
confidence: 99%
“…The protective role of dietary patterns rich in bioactive molecules, antioxidants, and food‐derived platelet‐activating factor (PAF) inhibitors, including those present in the Mediterranean diet are made effective by inhibiting PAF activities and/or modulating its metabolism towards homeostatic PAF levels, since the key to reduce CVD incidence is to effectively prevent the PAF/PAF‐R pathways and PAF synthesis towards homeostatic re‐equilibration of PAF levels and other inflammatory mediators via diet and healthy lifestyle (Tsoupras et al., 2018). A 10‐year epidemiological study has indicated that increasing adherence to Mediterranean diets reliably correlates with decreased CVD rates, particularly fatal and nonfatal myocardial infarction (Critselis et al., 2021). The other epidemiological report shows that the Mediterranean diet minimizes the occurrence of cardiovascular diseases by 30%, and inhibit the development of acute diabetes and improves glycemic regulation compared to control diet for diabetic patients (Kouvari et al., 2021).…”
Section: The Health Aspect Of the Mediterranean Dietmentioning
confidence: 99%
“…Cardiovascular diseases have high morbidity and mortality and have become the major cause of death worldwide [1]. Atherosclerosis is the major pathogenesis of cardiovascular disease and is characterized by lipid-loaded lesions in the vascular wall.…”
Section: Introductionmentioning
confidence: 99%